A Study of Handgrip Strength in Patients with Rheumatoid Arthritis: Its Correlations with Functional and Anthropometric Variables (Indian Journal of Public Health Research & Development, 2020)
Background: Rheumatoid arthritis (RA) is a chronic, systemic inflammatory disorder that primarily affectsthe small joints of hand. In the present study, hand grip strength was estimated on purposively selected 205patients with RA aged 25-65 years. Correlations of handgrip strength have also been studied with someanthropometric and functional variables in patients with RA.Materials and methods: The subjects were assessed for handgrip strength (both dominant and nondominant), two functional variables, i.e. pain and pain today, and eight anthropometric variables namely,height, weight, BMI, hand and upper arm circumferences, forearm, upperarm and total arm length withstandard techniques.Results: It was observed that the patients with RA had significantly lesser (p
Keywords: Handgrip strength, anthropometric variables, functional variables, patients with rheumatoid arthritis.